Analysis of solar photovoltaic penetration impact to low voltage distribution network and development of smart controls for voltage stability - Dilini Wasana Almeida (2023)
In recent years, solar photovoltaic (PV) systems have gained worldwide attention in the generation of greener energy. As a consequence, a significant number of PV systems are connected to low voltage (LV) distribution networks concerning the assurance of catering to the growing energy demand. However, the increased penetration of grid connected PV systems poses new technical challenges to the power system. The infringement of voltage limits attributed to reverse power flow has been recognized as one of the significant implications of high PV penetration. As these technical issues hinder the hosting capacity of networks, the Distribution Network Operators (DNOs) are required to enforce restrictions on the integration of new PV systems into the LV distribution grid and also to undertake network reinforcement, which eventually leads to substantial capital investment. Therefore, it is of vital importance to conduct an accurate assessment of the potential impacts of solar PV and to propose effective mitigation strategies, focusing on a smooth operation and optimal PV penetration. In this context, this thesis has focused to analyze the impact of solar PV penetration on LV distribution networks and developing smart controls and energy management schemes to ensure voltage statutory limits of the LV distribution network. In order to conduct a comprehensive analysis, detailed network models of three distinct LV distribution networks were developed and validated. The daily residential load profiles and irradiance profiles were adopted to perform minute-by-minute time-series power flow simulations, incorporating the real-time variations in PV generation and load demand. Both deterministic and Monte Carlo impact assessments were proposed to quantify the potential impacts under different PV penetration levels. In order to mitigate the overvoltage issues due to high PV integration, this research has contributed by presenting pragmatic and cost-effective voltage management schemes that would make use of existing equipment/assets and information. Thus, the off-load tap changer of LV distribution transformer, residential-scale PV systems, and battery energy storage systems were used to actively manage the grid voltage. The performance of the off-load tap changer of the LV distribution transformer was analyzed to provide effective overvoltage management under high PV penetration. A variety of local control functions of PV inverters such as power factor control, Volt-Var control, and Volt-Watt control were proposed and implemented to regulate the active and reactive power output of the PV inverter. Besides, the Volt-Var-Watt control that combines both active power curtailment and reactive power compensation of PV inverters was analyzed with the aim of enhancing the efficiency of the voltage regulation. Moreover, a decentralized, adaptive control strategy for residential-scale battery energy storage systems (RBESSs) was proposed to address overvoltage issues by dynamically adjusting the charge/discharge rates while making efficient use of the available storage capacity. Finally, the effectiveness of each mitigation technique was evaluated and quantified using several performance criteria. The results of the impact analysis established voltage rise as the dominant constraint which limits the capability of accommodating higher PV penetration levels in typical LV distribution networks. The findings revealed that the proposed mitigation techniques are successful in overcoming the overvoltage issues. In particular, the Volt-Var-Watt control of PV inverters was capable of providing an efficient voltage control with less impact on prosumers and DNOs. Furthermore, the proposed RBESS control strategy has shown effectiveness in alleviating the voltage rise issues while offering benefits to the prosumers by maximizing self-consumption.